Rancang Bangun Mesin Tanam Padi Dengan Menggunakan Pendekatan Quality Function Deployment - Hidayat, Khoirul; Mu'tamar, M Fuad Fauzul; Firmansyah, R. Arief (Teknik Industri, Fakultas Teknik, Universitas Hasyim Asy'ari, 2025)
Indonesia has various types of plants that can be cultivated throughout the year, such as rice, corn, soybeans, palm oil, coffee, tea, and cocoa. Rice is the most widely planted agricultural commodity and is a staple food for most Indonesians. Indonesian people still have extensive rice fields planted with rice. However, many young people now refuse to become farmers because they are considered unpromising to meet their needs. Therefore, it is necessary to research the design of rice planting machines. The purpose of this study is to design a rice planting machine according to the needs of farmers. The results of this study indicate that there are complaints from farmers during rice planting. Complaints are pain in body parts such as the neck, shoulders, waist, back, wrists, fingers, thighs, legs, and ankles. Therefore, it is necessary to design a rice planting machine to avoid complaints from farmers when planting rice.